The critical role of diet and nutrition in managing inflammatory bowel disease - Ghamdi, Khalid Mohammed Al; Alrahma, Husain Ali; Alkanhal, Faisal Abdulaziz; Alhamazani, Faisal Twairesh; Aloraini, Ebtehaj Saud; Alqadiri, Nahed Ghazi; Alhawsawi, Mohammed Zakaria; Thabet, Atyaf Ali; Ajzaji, Riyadh Jamil; Nasser, Jamal Saeed; Almarzooq, Hassan Mohammed; Bawareth, Rozana (International Journal Of Community Medicine And Public Health, 2023)
The persistent inflammation during inflammatory bowel disease (IBD) can severely harm the GI tract. There are several symptoms of IBD, which produce discomfort, frequent bowel movements, blood in stools, loss of weight, and tiredness, which have an impact on the lives of patients and their nutritional health. Managing IBD involves paying attention to diet and nutrition. It is important to identify trigger foods for each individual using methods like keeping food diaries or following plans recommended by dietitians that are low in residue or FODMAPs. Nutritional deficiencies, common in IBD, require attention to prevent malnutrition, muscle wasting, and complications. Having a proper dietary plan and accounting for disease characteristics and patient preferences is essential. Also, medication interactions are important during dietary monitoring. Dehydration, affecting many IBD patients, underscores the importance of maintaining fluid intake. An approach to managing IBD requires teamwork among healthcare professionals, dietitians, and patients. It involves customizing plans and combining them with medical treatments to achieve the best possible control over the disease.